SHAPING INTERFAITH PERSPECTIVES: AN ANALYSIS OF INDONESIAN YOUTH VIEWS ON TRUST, SOCIAL INTERACTION, AND POLITICAL INCLINATIONS ACROSS SECONDARY SCHOOL - Fatah, Anton Abdul; Huda, Miftahul (Jurnal Sosiologi Reflektif, 2023)
The objective of this research is to analyze the viewpoints of young Indonesians during their adolescence and adulthood about trust between different religions, social interaction, and political inclinations. Specifically, it emphasizes how the duration of secondary school education might shape their viewpoints. This study used ordinal logistic regression analysis to examine panel data collected from the Indonesian Family Life Survey, which comprises a sample size of over 20,000 respondents. The findings indicate a decrease in the standard of individuals' interfaith conduct between 2007 and 2014. The research indicates that those who finished secondary school during the New Order era exhibit higher levels of tolerance towards interfaith ideas in comparison to those who completed secondary school during the Reformation era. The disparity might be attributed to the policies of the New Order administration, which prioritized national cohesion and stability while actively opposing religious "extremism". The research findings indicate that those who finished secondary school during the post-New Order era have a heightened inclination towards interfaith political socialization and preferences. The results of this study hold significant relevance in the current climate of growing intolerance and religious division, particularly with regards to the determinants of interfaith attitudes and behavior, as well as the role of education in fostering ideals of tolerance. Hence, this study underscores the necessity for additional longitudinal and comparative research on interfaith community interactions, including a broader spectrum of age cohorts and geographical areas.Penelitian ini bertujuan untuk mengulas perspektif generasi muda Indonesia pada usia remaja dan dewasa pada kepercayaan (trust), sosialisasi, dan preferensi politik lintas agama. Secara khusus, penelitian ini menyoroti bagaimana masa pendidikan sekolah menengah dapat memengaruhi perspektif mereka. Melalui analisis regresi logistik ordinal, penelitian ini menganalisis data panel yang diperoleh dari Survei Kehidupan Keluarga Indonesia, yang mencakup lebih dari 20.000 responden. Hasil penelitian menunjukkan adanya penurunan kualitas perilaku lintas agama masyarakat pada tahun 2007 hingga 2014. Data penelitian ini memperlihatkan bagaimana generasi muda yang menyelesaikan sekolah menengah pertama pada masa Orde Baru menunjukkan penerimaan yang lebih besar terhadap kepercayaan lintas agama dibandingkan dengan mereka yang menempuh pendidikan sekolah menengah di masa Reformasi. Perbedaan ini mungkin disebabkan oleh kebijakan rezim Orde Baru yang menitikberatkan pada pentingnya persatuan dan stabilitas nasional serta cenderung menentang 'ekstremisme' agama. Penelitian ini juga menunjukkan bahwa sebagian besar masyarakat yang menyelesaikan pendidikan SLTP/SLTA pasca Orde Baru menunjukkan kecenderungan yang lebih besar dalam aspek sosialisasi dan preferensi politik lintas agama. Temuan penelitian ini juga sangat penting dalam konteks meningkatnya intoleransi dan polarisasi agama saat ini, terutama terkait faktor-faktor yang mempengaruhi sikap dan perilaku antarumat beragama dan pentingnya pendidikan dalam mempromosikan nilai-nilai toleransi. Oleh karenanya, penelitian ini menekankan perlunya kajian longitudinal dan komparatif lanjutan tentang hubungan masyarakat lintas agama yang mencakup rentang kelompok usia dan wilayah yang lebih luas.